Pelatihan Pembuatan Minuman Herbal untuk Immune Booster Staff Kebun Raya Liwa Di Masa Pandemi Covid-19 - Setyaningrum, Endah; Widiastuti, Endang Linirin; Arifiyanto, Achmad (PUSAT PENELITIAN DAN PENGABDIAN PADA MASYARAKAT (PPPM) POLITEKNIK NEGERI SAMBAS, 2022)
The Sars-Cov2 virus, also known as the Covid-19 pandemic, has led in a rise in the usage of immune-boosting supplement items. This situation resulted in higher prices and a scarcity of stock on the market. This program seeks to motivate and educate UPT Liwa Botanical Garden (KRL) employees about the necessity of utilizing herbs to boost body ’s immune system during the Covid-19 outbreak. The activity's target audience is workers, who interact often with tourists from various locations. Twenty persons participated, including KRL officials, Lumbok Seminung Kehati Park Managers, and KRL apprentice students. This activity takes the form of providing content, question and answer sessions, demonstrations on how to make herbal beverages, and training assessment using pre and post-test questionnaires. The results of the training implementation revealed an increase in participants' motivation and understanding of the importance of herbal functions and the skills of making herbal drinks, as evidenced by their enthusiasm in the discussion both before and after the demonstration of making herbal drinks.